Dressed for Death: Gender, Respectability, and Resistance at the Gallows. Issue 2 (23rd August 2021) - Linders, Annulla; Casanova, Erynn Masi de; Shupe, Kyle
Abstract : In this paper we examine the dress of execution victims. Executions provide both the convict and the state with an opportunity to claim honor and respectability. Drawing on newspaper accounts of executions conducted between 1840 and 1940, we demonstrate that convict attire reveals an important tension between the convicts' gendered character claims and the efforts by execution managers to arrange a credible execution. But whereas displays of masculinity reinforce more than challenge the propriety of executions, women's femininity displays challenge not only the propriety of executions, but also the respectability of those tasked with their killing. We conclude that the subversive potential of clothing is found not only in the garments themselves, nor only on the wearers' intentions, but also on the institutional settings in which they are presented.